A discourse-analytic framework for conversational engagement in online discussion tasks, part 2: level of analytic depth - O'ROURKE, BREFFNI; MARTIN, GILLIAN; O'Sullivan, Helen (My University, 2015)
What do we mean by “engagement” in the context of online discussions? How do we recognise it? Is it quantifiable? Can we find ways of analysing it that might be of assistance to task designers, instructors, and students? This work is concerned with a discourse-analytic framework for characterising collaborative topic engagement in online, text-based communicative tasks. The framework comprises a two-tier analysis. Tier 1, presented in O’Rourke, Martin & O’Sullivan (2014), categorises act types, and deals with topic development through engagement with others’ contributions, using Van Lier’s (1996) conception of contingency in discourse. The present paper develops the framework by introducing Tier 2, which is concerned with analytical depth in learners’ conversational contributions. The data are taken from Speakwise, a long-running, blended telecollaborative exchange between Trinity College Dublin and the University of Hildesheim. On the Irish side, the exchange is embedded within a course in intercultural communication offered to final-year students of German. The framework is intended to be useful to online task designers for defining desirable discourse outcomes; to instructors, for monitoring and facilitating online discourse; and to learners, for reflecting on the quality of their engagement with tasks, within-institution peers, and telecollaborative partners. REFERENCES O’Rourke, B., G. Martin, and H. O’Sullivan, 2014. A discourse analytic framework for conversational engagement in online discussion tasks. Paper presented at Eurocall 2014, Groningent. Van Lier, L., 1996. Interaction in the language curriculum : awareness, autonomy, and authenticity. London: Longman.
Eurocall 2015
Paper presented at Eurocall 2015, Padova
Keywords: computer-assisted language learning; online language learning; synchronous computer-mediated communication; SCMC; discourse analysis; argumentation; dialogue; conversation analysis; second and foreign language learning; Identities in Transformation; Intelligent Content & Communications; Telecommunications; Classroom Discourse; Conversation and discourse analysis; Discourse & Dialogue; Discourse analysis; Information technology in education; Pragmatics; Technology and communication; online chat; synchronous computer-mediated communication